"Multisystem Inflammatory Syndrome in Children"-Like Disease after COVID-19 Vaccination (MIS-V) with Potential Significance of Functional Active Autoantibodies Targeting G-Protein-Coupled Receptors (GPCR-fAAb) for Pathophysiology and Therapy. - Schmidt, Marius; Hébert, Steven; Wallukat, Gerd; Ponader, Rolf; Krickau, Tobias; Galiano, Matthias; Reutter, Heiko Martin; Wölfle, Joachim; Agaimy, Abbas; Mardin, Christian; Hörning, André; Hohberger, Bettina (Children, 2023)
BACKGROUND: An infection with SARS-CoV-2 can trigger a systemic disorder by pathological autoimmune processes. A certain type of this dysregulation is known as Multisystemic inflammatory syndrome in children (MIS-C). However, similar symptoms may occur and have been described as Multisystemic inflammatory syndrome after SARS-CoV-2 Vaccination (MIS-V) following vaccination against SARS-CoV-2. We report the case of a 12-year-old boy who was identified with MIS-C symptoms without previous SARS-CoV-2 infection after receiving two doses of the Pfizer-BioNTech COVID-19 vaccine approximately one month prior to the onset of symptoms. He showed polyserositis, severe gastrointestinal symptoms and, consequently, a manifestation of a multiorgan failure. IgG antibodies against spike proteins of SARS-CoV-2 were detected, indicating a successful vaccination, while SARS-CoV-2 Nucleocapsid protein antibodies and SARS-CoV-2 PCR were not detected. Several functional, active autoantibodies against G-protein-coupled receptors (GPCR-fAAb), previously associated with Long COVID disease, were detected in a cardiomyocyte bioassay. Immunosuppression with steroids was initiated. Due to side effects, treatment with steroids and later interleukin 1 receptor antagonists had to be terminated. Instead, immunoadsorption was performed and continued with tacrolimus and mycophenolic acid therapy, leading to improvement and discharge after 79 days. GPCR-fAAb decreased during therapy and remained negative after clinical curing and under continued immunosuppressive therapy with tacrolimus and mycophenolic acid. Follow-up of the patient showed him in good condition after one year. CONCLUSIONS: Infection with SARS-CoV-2 shows a broad and severe variety of symptoms, partly due to autoimmune dysregulation, which, in some instances, can lead to multiorgan failure. Despite its rarity, post-vaccine MIS-C-like disease may develop into a serious condition triggered by autoimmune dysregulation. The evidence of circulating GPCR-fAAb and their disappearance after therapy suggests a link of GPCR-fAAb to the clinical manifestations. Thus, we hypothesize a potential role of GPCR-fAAb in pathophysiology and their potential importance for the therapy of MIS-C or MIS-V. However, this observation needs further investigation to prove a causative correlation.
EVALuna2:547545

“Multisystem Inflammatory Syndrome in Children” (MIS-C) after COVID-19 Infection in the Metropolitan Area of Nuremberg-Erlangen, Germany—Expectations and Results of a Two-Year Period - Hébert, Steven; Schmidt, Marius; Topf, Georg; Rieger, Daniel; Klinge, Jens; Vermehren, Jan; Fusch, Christoph; Grillhösl, Christian; Schroth, Michael; Toni, Irmgard; Reutter, Heiko Martin; Morhart, Patrick; et al. (Children, 2023)
Background: Multisystemic Inflammatory Syndrome in children (MIS-C) is a rare autoimmune disorder occurring after a latency period following acute SARS-CoV-2 infection. The therapeutic regime of MIS-C is adapted to the therapy of the Kawasaki disease, as clinical symptoms are similar. Since the Kawasaki disease can potentially result in severe symptoms, which may even affect long-term health, it is essential to gain further knowledge about MIS-C. Thus, we aimed to investigate the incidence, symptoms, therapeutical procedure and outcome of MIS-C patients in the metropolitan area of Nuremberg-Erlangen during the SARS-CoV2 pandemic. Material and Methods: Retrospective analysis of clinical charts of MIS-C patients was carried out at three children’s hospitals covering the medical care of the metropolitan area of Nuremberg-Erlangen in Germany. Demographic characteristics and symptoms at first visit, their clinical course, therapeutic regime and outcome were recorded within the time period January 2021–December 2022. Results: Analysis of 10 patients (5 male, 5 female) with MIS-C resulting in an incidence of 2.14/100.000 children. The median time between COVID-19 infection and admission to hospital was 5 weeks. The median age was 7 years. Symptoms comprised fever (100%), rash (70%), bilateral non-purulent conjunctivitis (70%) and urticaria (20%). At the time of presentation, diagnosis-defining inflammation parameters were increased and the range for C-reactive protein was 4.13 mg/dL to 28 mg/dL, with a median of 24.7 mg/dL. Procalcitonin was initially determined in six patients (1.92 ng/mL to 21.5 ng/mL) with a median value of 5.5 pg/mL. Two patients displayed leukocytosis and two displayed leukopenia. None of the patients presented coronary pathologies. Nine of the ten patients received intravenous immunoglobulin (IVIG) therapy. In addition, patients received intravenous steroids (80%) and acetylsalicylic acid (80%). Conclusion: SARS-CoV virus may rarely exert multiorgan manifestations due to hyperinflammatory immunological processes. Within two years of the COVID-19 pandemic, we identified ten patients with COVID-induced MIS-C in the metropolitan area Nuremberg-Erlangen. In the description of the patient collective, we can confirm that MIS-C is distinguished from the Kawasaki disease by the lack of coronary manifestations. Interestingly, although having monitored all pediatric facilities in the investigated area, we find lower incidences of MIS-C compared to findings in the literature. In conclusion, an overestimation of incidences in the upcoming MIS-C during the pandemic needs to be considered.
CRIS-Team Scopus Importer:2023-09-08
Keywords: COVID-19; intravenous immunoglobulins; IVIG; mAbs; MIS-C; monoclonal antibodies; Multisystem Inflammatory Syndrome in children

No evidence of the unfolded protein response in the placenta of two rodent models of preeclampsia and intrauterine growth restriction - Denkl, Barbara; Cordasic, Nada; Hübner, Hanna; Menendez-Castro, Carlos; Schmidt, Marius; Mocker, Alexander; Wölfle, Joachim; Hartner, Andrea; Fahlbusch, Fabian (Biology of Reproduction, 2021)
In humans, intrauterine growth restriction (IUGR) and preeclampsia (PE) are associated with induction of the unfolded protein response (UPR) and increased placental endoplasmic reticulum (ER) stress. Especially in PE, oxidative stress occurs relative to the severity of maternal vascular underperfusion (MVU) of the placental bed. On the premise that understanding the mechanisms of placental dysfunction could lead to targeted therapeutic options for human IUGR and PE, we investigated the roles of the placental UPR and oxidative stress in two rodent models of these human gestational pathologies. We employed a rat IUGR model of gestational maternal protein restriction, as well as an endothelial nitric oxide synthase knockout mouse model (eNOS-/-) of PE/IUGR. Placental expression of UPR members was analyzed via qRT-PCR (Grp78, Calnexin, Perk, Chop, Atf6, and Ern1), immunohistochemistry, and Western blotting (Calnexin, ATF6, GRP78, CHOP, phospho-eIF2α, and phospho-IRE1). Oxidative stress was determined via Western blotting (3-nitrotyrosine and 4-hydroxy-2-nonenal). Both animal models showed a significant reduction of fetal and placental weight. These effects did not induce placental UPR. In contrast to human data, results from our rodent models suggest retention of placental plasticity in the setting of ER stress under an adverse gestational environment. Oxidative stress was significantly increased only in female IUGR rat placentas, suggesting a sexually dimorphic response to maternal malnutrition. Our study advances understanding of the involvement of the placental UPR in IUGR and PE. Moreover, it emphasizes the appropriate choice of animal models researching various aspects of these pregnancy complications.
CRIS-Team Scopus Importer:2021-08-27
Keywords: eNOS; ER stress; IUGR; oxidative stress; placenta; preeclampsia